Family Matters: The Impact of Traditional and Egalitarian Gender Role Messages on Sexual and Gender Minority Latinx Adults' Alcohol Use and Sexual Risk. Issue 5 (13th June 2022) - Yamasaki, Vic; Le, Thomas P.
ABSTRACT: Latinx sexual and gender minority individuals are at increased risk for engaging in risky sexual behavior given the intersection of their sexual orientation and ethnic identities. Many studies have found that sexual and gender minority Latinx folks experience nonacceptance and discrimination from within their families due to their identity. However, none have explored how underlying familial beliefs, such as traditional and egalitarian gender roles, influence sexual and gender minority Latinx adults' risky sexual behavior. Within a sample of 168 Latinx sexual and gender minority individuals, the present study examined the indirect effect of receiving traditional and egalitarian parental gender role messages on risky sexual behavior through alcohol use and internalized stigma related to their sexual and gender minority identity. Results showed that traditional gender role messages were indirectly associated with increased risky sexual behavior through increased alcohol use, whereas no such indirect effect was found through internalized stigma. Receiving egalitarian gender role messages was not associated with risky sexual behaviors. Findings from this paper can be used to tailor community outreach programs that aim to reduce sexual risk behaviors and alcohol use in the Latinx sexual and gender minority community as a result of traditional parental gender role messages.